Compare Analysis Between Chinese and Indonesian Phonetics and Teaching Suggestion - Lydia Anggreani (Humaniora, 2014)
With further development of friendly relations between China and Indonesia, coupled with a growing number of Indonesian Chinese, learning Chinese language is getting more important. Article compared Chinese and Indonesian voice and showed the voice of the Chinese language. Moreover, article provided ideas forChinese phonetics teaching and for Indonesian students in learning Chinese pronunciation. In addition, article puts forward suggestions in order to improve foreign language teaching.